PENGARUH VARIABEL KEPUASAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), DAN TRUST IN LEADER TERHADAP KINERJA PEGAWAI - Anwar Anwar; Budi Santosa (STIE Mandala Jember, 2014)
This study aims to determine the effect of job satisfaction, organizational citizenship behavioral and trust in the leader on employee performance. The variables used in this study are job satisfaction, organizational citizenship behavioral, trust in the leader and employee performance. The study was conducted at educational institutions Muhammadiyah Jember. The population is all employees and faculty at educational institutions in the Muhammadiyah Jember. With a total sample of 200 people consisting of employees and faculty members in the Institute of Education in Muhammadiyah Jember. The analytical method used is multiple linear regression analysis. The results showed that job satisfaction and citizenship behavioral organzational effect on employee performance. While trust in the leader does not affect the employee's performance.